NPS 2143, a selective calcium-sensing receptor antagonist inhibits lipopolysaccharide-induced pulmonary inflammation. (October 2017) - Lee, Jae-Won; Park, Hyun Ah; Kwon, Ok-Kyoung; Park, Ji-Won; Lee, Gilhye; Lee, Hee Jae; Lee, Seung Jin; Oh, Sei-Ryang; Ahn, Kyung-Seop
Graphical abstract: Highlights: This is the first report demonstrating that NPS 2143 inhibits LPS-induced pulmonary inflammation in mice. NPS 2143 alleviates the influx of inflammatory cells and the production of inflammatory mediators. NF-κB and AMPK are involved in NPS 2143-medicated inhibition of pulmonary inflammation. Abstract: NPS 2143, a novel and selective antagonist of calcium-sensing receptor (CaSR) has been reported to possess anti-inflammatory activity. In the present study, we examined the protective effect of NPS 2143 on lipopolysaccharide (LPS)-induced acute lung injury (ALI). NPS 2143 pretreatment significantly inhibited the influx of inflammatory cells and the expression of monocyte chemoattractant protein-1 (MCP-1) in the lung of mice with LPS-induced ALI. NPS 2143 decreased the levels of neutrophil elastase (NE) and protein concentration in the bronchoalveolar lavage fluid (BALF). NPS 2143 also reduced the production of inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in the BALF and serum. In addition, NPS 2143 attenuated the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), and increased the activation of AMP-activated protein kinase (AMPK) in the lung. NPS 2143 also downregulated the activation of nuclear factor-kappa B (NF-κB) in the lung. In LPS-stimulated H292 airway epithelial cells, NPS 2143 attenuated the releases of IL-6 and MCP-1. Furthermore, NPS 2143 upregulated the activation of AMPK and downregulated the activation of NF-κB. These results suggest that NPS 2143 could be potential agent for the treatment of inflammatory diseases including ALI.